Rekonstruksi Model the Strategic Triangle: Perspektif Tradisi Bau Lolon - Ethelbert, Yohanes Kornelius; Indriyati, Indriyati; Molan, Kristianus (Journal of Education on Social Science (JESS), 2024)
Moore developed the strategic triangle to aid public managers in designing policies that align with public needs. The strategic triangle is a way for governments to create policies based on the values desired by citizens. This strategy includes three important elements, including public value outcomes, authorizing environment and operational capacity. Nonetheless, certain experts deem this concept to have critical limitations that require conceptual resolution. Regrettably, none of their criticisms provide a solution towards the concept's improvement. Using qualitative research with an ethnographic approach, this study aims to construct and critique a new model of the strategic triangle concept, utilizing the local wisdom of the bau lolon ritual as an alternative solution. The central focus of this research examines the relevance of moral values within the bau lolon ritual as a possible alternative means of mitigating the weaknesses of the strategic triangle concept. Bau lolon ritual is usually performed by the Lamaholot people who inhabit the eastern part of the island of Flores in the province of East Nusa Tenggara, Indonesia.The findings indicate that the implementation of bau lolon rituals can surpass the constraints of the previous model by incorporating principles of fairness, integrity, and camaraderie in the decision-making process.